A versatile method for producing functionalized cellulose nanofibers and their application. Issue 6 (27th January 2016) - Huang, Pei; Zhao, Yang; Kuga, Shigenori; Wu, Min; Huang, Yong
Abstract : Individual dispersed cellulose nanofibers can be produced through ball milling by adding anhydride and DMAP in one step. By altering the type of anhydride, the cellulose nanofiber presents different surface properties and tailored compatibility with varied solvents or matrices, which greatly promote the massive applications of cellulose nanofibers. Abstract : A facile method was developed to produce functionalized cellulose nanofibers in one step by ball milling. Through the synergy of mechanical and chemical actions, the produced cellulose nanofibers are ca. 20 nm wide and several micrometers long, with surface properties tailored by choice of modifying reagent. Modified by succinic anhydride, a cellulose nanofiber shows enhanced hydrophilicity, can be readily dispersed in water or DMSO, and gives a zeta potential of −38.7 mV due to carboxyl groups on the surface. Modified by dodecyl succinic anhydride, a cellulose nanofiber has excellent dispersibility in o -xylene and good compatibility with polyethylene. The polyethylene-cellulose nanofiber composite presents overall enhancement of mechanical properties. This method opens a new way to the production of functionalized cellulose nanofibers.